2012
DOI: 10.3402/tellusa.v64i0.17224
|View full text |Cite
|
Sign up to set email alerts
|

Perturbing the potential vorticity field in mesoscale forecasts of two Mediterranean heavy precipitation events

Abstract: A B S T R A C TIn order to improve the quality of the Mediterranean high-impact weather (HIW) numerical predictions, this study proposes to modify the potential vorticity (PV) field of the model initial state, taking advantage of information provided by the water vapour (WV) channel of the METEOSAT-7 satellite. The implemented PV field modifications aim to reduce the mismatch between the upper-level PV features and the WV brightness temperatures guided by the known relation between these two fields (PV-WV tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…A thorough verification of the results showed that even though all EPS are skilful and advantageous over a deterministic approach, both PV-perturbed systems beat a multiphysics approach, the PV gradient being the best. Vich et al (2012) introduced a novel concept consisting of building the ensemble members with the previous approach plus subjectively defined perturbations, drawn by a forecaster or an expert.…”
Section: Forecasting Methods: Testing Ensemble Prediction Systems (Eps)mentioning
confidence: 99%
“…A thorough verification of the results showed that even though all EPS are skilful and advantageous over a deterministic approach, both PV-perturbed systems beat a multiphysics approach, the PV gradient being the best. Vich et al (2012) introduced a novel concept consisting of building the ensemble members with the previous approach plus subjectively defined perturbations, drawn by a forecaster or an expert.…”
Section: Forecasting Methods: Testing Ensemble Prediction Systems (Eps)mentioning
confidence: 99%